Seasonal Changes and Children with Bronchial Asthma (2—15 Years Age) Reporting at Asthma Clinics of Mayo Hospital and Children Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Background: Bronchial Asthma is among the common chronic illnesses of childhood and one of major causes of absence from school. It is a multi-factorial condition determined by an interaction of genetic and environmental factors.Objective: To document the change in frequency with change in season of bronchial asthma cases  (2-15 years) presenting at two tertiary care hospitals in Lahore and advise parents to take preventive measures.Methodology: A cross-sectional descriptive study was carried out for a period of one year (2002-03) at Mayo Hospital and Children Hospital & Institute of Child Health Lahore. Cases of asthma attending asthma clinics of both hospitals were included in the study. Both seasonal factors (monthly mean temperature & relative humidity of the environment) and outdoor air pollutants were studied for finding out such association.Result: Out of all asthma cases (n=1135) of both hospitals, reported during the study period, 70.1% had age of 5 to 15 years with male to female ratio 2:1. Maximum cases (n=173) reported in October and minimum (n=42) in February, corresponding with variations in temperature, relative humidity and air pollutants.Conclusion: More cases visited asthma clinic during hot and humid as well as colder and dry months with higher levels of air pollutants. Parents are advised to take preventive measures to avoid precipitation of bronchial asthma during these months of calendar year.
Keywords: Seasonal Factors, Air Pollutants, Bronchial Asthma, Children